Perceived Differences in the Management of Mental Health Patients in Remote and Rural Australia and Strategies for Improvement: Findings from a National Qualitative Study of Emergency Clinicians. (11th April 2011) - Jelinek, G. A.; Weiland, T. J.; Mackinlay, C.; Hill, N.; Gerdtz, M. F.
Abstract : Introduction . We aimed to describe perceptions of Australian emergency clinicians of differences in management of mental health patients in rural and remote Australia compared with metropolitan hospitals, and what could be improved. Methods . Descriptive exploratory study using semi-structured telephone interviews of doctors and nurses in Australian emergency departments (EDs), stratified to represent states and territories and rural or metropolitan location. Content analysis of responses developed themes and sub-themes. Results . Of 39 doctors and 32 nurses responding to email invitation, 20 doctors and 16 nurses were interviewed. Major themes were resources/environment, staff and patient issues. Clinicians noted lack of access in rural areas to psychiatric support services, especially alcohol and drug services, limited referral options, and a lack of knowledge, understanding and acceptance of mental health issues. The clinicians suggested resource, education and guideline improvements, wanting better access to mental health experts in rural areas, better support networks and visiting specialist coverage, and educational courses tailored to the needs of rural clinicians. Conclusion . Clinicians managing mental health patients in rural and remote Australian EDs lack resources, support services and referral capacity, and access to appropriate education and training. Improvements would better enable access to support and referral services, and educational opportunities.